2015
DOI: 10.1016/j.bcmd.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MXD3 induces apoptosis of Reh human precursor B acute lymphoblastic leukemia cells

Abstract: MXD3 is a transcription factor that plays an important role in proliferation of human DAOY medulloblastoma cells. Here, we demonstrate that MXD3 is highly enriched in human precursor B acute lymphoblastic leukemia (preB ALL) samples compared to mobilized peripheral blood mononuclear cells, bone marrow, or hematopoietic stem cells from healthy donors. MXD3 knock-down in the preB ALL cell line Reh resulted in decreased cell numbers with no change in G0/G1, S or G2/M populations but increased apoptosis compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
(26 reference statements)
4
21
0
1
Order By: Relevance
“…The mechanism of action of the αCD22-ASO conjugate remains unclear since the rapid kinetics of MXD3 protein knockdown is not consistent with inhibition of MXD3 mRNA levels (data not shown). Interestingly, the same phenomenon (early MXD3 protein knockdown without confirmation of mRNA knockdown) was observed with several different MXD3 ASO sequences (data not shown), as well as MXD3 siRNA (47,48), with or without αCD22 Ab as a vehicle. These data suggest that the ASO conjugate may mediate MXD3 translational inhibition and thus would explain the inability to detect a reduction in MXD3 transcript levels (59,60).…”
Section: Acknowledgmentssupporting
confidence: 68%
See 1 more Smart Citation
“…The mechanism of action of the αCD22-ASO conjugate remains unclear since the rapid kinetics of MXD3 protein knockdown is not consistent with inhibition of MXD3 mRNA levels (data not shown). Interestingly, the same phenomenon (early MXD3 protein knockdown without confirmation of mRNA knockdown) was observed with several different MXD3 ASO sequences (data not shown), as well as MXD3 siRNA (47,48), with or without αCD22 Ab as a vehicle. These data suggest that the ASO conjugate may mediate MXD3 translational inhibition and thus would explain the inability to detect a reduction in MXD3 transcript levels (59,60).…”
Section: Acknowledgmentssupporting
confidence: 68%
“…MAX dimerization protein 3 (MXD3) is a basic-helix-loop-helix-leucine-zipper transcription factor that is part of the v-myc avian myelocytomatosis viral oncogene homolog (MYC)/MAX/MXD transcriptional network involved in cellular proliferation (44)(45)(46). Previously, we demonstrated that MXD3 functions as an anti-apoptotic protein and that knockdown of MXD3 can be a novel effective therapeutic strategy for preB ALL in vitro (47,48). In this study, we developed a novel leukemia-targeting compound using MXD3 ASO conjugated to anti-CD22 Ab (αCD22 Ab) for preB ALL.…”
Section: Cd22 Ab-aso Conjugatementioning
confidence: 99%
“…To confirm that the higher levels of apoptosis we observed were indeed due to MXD3 knockdown and not off-target effects, we tested the treatment on SK-N-DZ cells expressing a rescue construct coding for knockdown-insensitive, wild-type MXD3 ( 9 ). SK-N-DZ cells were stably transduced using lentiviral vectors expressing MXD3 shRNA and the rescue sequence (shMXD3Rescue), MXD3 shRNA alone (shMXD3), or a negative control shRNA (shControl) designed to not knockdown any known human gene.…”
Section: Resultsmentioning
confidence: 91%
“…Since monotherapy does not work for most cancers, an ideal therapy should include multiple molecular-targeted approaches. Previously, we identified the transcription factor MXD3 as a novel target for precursor B-cell acute lymphoblastic leukemia (preB ALL) ( 9 11 ). MXD3 is a member of the family of Mad proteins that interact with Max proteins ( 12 ) and is reported to play a role in medulloblastoma tumorigenesis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Precursor B-acute lymphoblastic leukaemia (pre B-ALL) is the most prevalent phenotype of ALL, and T-acute lymphoblastic leukaemia (T-ALL) associated with a poor outcome [ 3 , 4 ]. However, current standard treatment consists of combination chemotherapy that is highly toxic to growing children, both in short and long terms [ 5 7 ]. To avoid serious side effects in chemotherapy and improve survival rates, novel anticancer agents are needed to address the emerging problem.…”
Section: Introductionmentioning
confidence: 99%